Microalgae Biotechnology: Methods and Applications - Xianmin Wang; Songlin Ma; Fantao Kong (Bioengineering)
Microalgae are regarded as sustainable and promising chassis for biotechnology due to their efficient photosynthesis and ability to convert CO2 into valuable products [...]